Alterações persistentes de colesterol total e LDL-Colesterol em crianças em tratamento da desnutrição: consequências da programação metabólica? - Alves, Jullyana Flávia da Rocha (2012)
The coexistence of malnutrition and dyslipidemia in the pediatric population is a recent find and is closely related to metabolic and endocrine changes occurring in early intrauterine life and / or early childhood. Malnourished children have reduced levels of insulin growth factor-like (IGF-1) and high serum concentrations of growth hormone (GH) that lead to a decrease in stature. This condition promotes a reduction in basal metabolic rate through increased respiratory quotient and low rate of lipid oxidation, which promotes increased waist / hip ratio and the development of chronic diseases in adult life. Fatty liver found in malnourished children is supposed to be related to changes in structure and function of hepatocytes occurred during pregnancy and / or in early childhood which permanently affect the synthesis of cholesterol and LDLC and its plasma concentrations. The persistent hypercholesterolemia observed in these children favors the accumulation of fat in the intra-abdominal, which is an independent risk factor for hypertension, type 2 diabetes, coronary heart disease and strokes. The literature suggests that the recovery centers and nutrition education can retrieve the childhood undernutrition the damages associated with it, provide for a balanced nutrition of macro and micronutrients in conjunction with a healthy environment and nutrition education. Within this context, the present study was to evaluate the biochemical profile of malnourished children at the Center for Nutritional Recovery and Education in the city of Maceió / Alagoas, between the years 2008 to 2011. To this end, we analyzed the medical records of 263 moderately malnourished children (Z score ≤ -2 SD) and severe (score ≤ Z-3s), aged between 12 and 71 months. In this study, it was found that treatment in the center offered improved IGF-1 by determining an increase in growth in malnourished children. There was also a reduction in triglyceride levels and increased HDL-C, the latter being statistically significant in children three years and more follow-up. However, the CT values of total and LDL-C were maintained above the desired levels during the treatment. It follows therefore that short stature observed in these children may be recovered and the levels of TG and HDL-C, but there was no normalization in the levels of total cholesterol and LDL-C, because even children at high (score Z ≤ -1.5 SD) maintained high levels of this lipid.